The essential role of YAP O-GlcNAcylation in high-glucose-stimulated liver tumorigenesis - Xiao Zhang (Nature Portfolio, 2017)
Yap is a transcriptional factor involved in tumorigenesis. Here the authors show that a previously unknown post-translational modification of Yap, O-GlcNAcylation, increases its transcriptional activity and is required for high glucose-induced liver cancer development.